B39 The Effect Of Huntingtin Gene Cag Repeat Expansion On Human Induced Pluripotent Stem Cell Neuronal Differentiation. (17th September 2014) - Sanders, P; Straccia, M; Joy, S; Comella Bolla, A; Bombau, G; Svendsen, C; Kemp, PJ; Allen, ND; Canals, JM
Abstract : Cell therapy is a key strategy in regenerative medicine to replace damaged tissues, and is a viable approach for treating Huntington's disease (HD) where specific degeneration of striatal GABAergic medium spiny neurons (MSNs) occurs as a consequence of expansion of the CAG repeats region of the htt gene. Implementation of cell replacement strategies using pluripotent stem cells requires development and characterisation of new differentiation protocols as previously described protocols are long and produce MSNs at a low efficiency. In this study we use a recently developed neuronal differentiation protocol which generates a significant level of MSN-like neurons from human embryonic stem cells, and apply it to induced pluripotent stem cell (iPSC) lines derived from HD and control patients. We characterise the progress of the iPSC lines through differentiation at the protein level by immunocytochemistry, and at the gene expression level using a customised quantitative PCR platform that monitors expression of 112 genes specific for neural developmental stages and/or encephalic areas. At the later stages of the protocol we assess functionality of the neurons. We observe clear differences in the rate at which different iPSC lines progress through differentiation with each cell line displaying a different gene expression profile. Some of the iPSC lines produce neurons expressing key MSN markers to a lesser or greater extent, with calcium signalling imaging indicating that this protocol generates a high number of functional neurons. Our results show that this differentiation protocol generates MSNs at a level comparable to or better than previously described protocols in a shorter time. Also we observe that CAG repeat expansion alters the rate of iPSC differentiation as well as potentially influencing MSN development and functionality.